Qualitative to quantitative study for solid waste management - Kabbashi, Nassereldeen Ahmed; Daoud, Jamal Ibrahim; Mirghani, Mohamed Elwathig Saeed; Mohd Kasim , Norliana Hanani (IDOSI Publication, 2013)
Organizations that manage the solid waste at certain designated areas sometimes neglect the environmental elements when they carry out their collection of solid waste activities. For instance, the leachate that sips out from the garbage collected either of residential or commercial area. Therefore, implementation of ISO 14001 standards in solid waste management companies are vital especially in Malaysia to protect the environment, prevent pollution and improve environmental performance. ISO 14001 has been implemented widely however in Malaysia; the percentage of organizations implementing this standard is way too small which is only 0.46%. This study was carried out to determine and analyze the adoption of ISO 14001 standard especially in Malaysian organization. Both certified and uncertified companies will be compared as to identify the difference of the implementation of ISO 14001. Qualitative research was carried out through personnel interviews and questionnaires. Visual Basic expert system will be used as a tool to aid the company to achieve their environmental mission step by step. The objectives had been achieved. Expert system that had been developed is a tool that will ease the organization in assessing the level of compliance according to the ISO 14001 standard. Strategies have been recommended for the ease of implementing ISO 14001 in the organization